Training of the future tourist guides for intercultural communicative interaction within professional activity - Kovalenko, Oleksandr V.; Yepyk, Larysa I.; Yeromenko, Andrii Yu.; Kashynska, Olena Ye.; Bezruchenkov, Yurii V. (Linguistics and Culture Review, 2021)
This study argues for the significance of the cultural approach to the professional training of the future tourist guide for intercultural communicative interaction. Notably, meeting the constantly growing needs of the tourist market consumer is a pressing issue. It is emphasised that the professional training of a specialist in this field should be focused on providing a high quality theoretical and practical training for a specialist to be ready for professional and communicative interaction with consumers of tourist services. Intercultural communication is seen as a purposeful connection between different cultures, which performs an exchange of information, cultural and spiritual value through professional activities to meet the needs of tourists, while taking into account the uniqueness of every culture. When interacting with the audience, the guide uses methods of pedagogical influence, which are based on didactic principles (scientific, ideological, connection with real life, accessibility, system, responsiveness and persuasiveness). They define the content, organisation and methods of educating tourists during the excursion, regardless of them being children or adults. The excursion method is the basis of the tour and is a compilation of the ways for the guide to share the knowledge and tourists’ reception of this knowledge.